Duterte Exlusion from Matobato case 'unfortunate but welcome' (2017)
President Rodrigo R. Duterte is excluded from the list of respondents in the Matobato case.
Keywords: Duterte, Rodrigo R; Matobato, Edgar; Trillanes, Antonio F., IV